RESISTING FRANCHISE CORPORATE CONTROL: HOW THE INTERNET ENABLES LOCAL PRACTICES IN POKÉMON PLAY - Kempton, Allen (AoIR Selected Papers of Internet Research, 2023)
Despite being a friendly face for children and an ambassador brand for Japan, Pokémon has always had a strong corporate side. As the Internet and technologies for hacking and communication became more available, players became more disillusioned about the friendliness of Pokémon as a franchise. The controlling nature of Game Freak along with the growing perception of lack of respect for its consumers has created a negative perception of the corporate aspect of the franchise. As a result, a global duality emerged; a corporate, franchise centered component versus a fan based, community-driven culture. In the global nature of Pokémon, where then does the local fit in? How do local Canadian players perceive, negotiate, and resist the corporate and global cultures to make their own play practices?This study examines ways in which the global aspect of Pokémon, both the corporate side and the community culture, influence the play practices of local Canadian players. Through one-on-one interviews, adult Pokémon players who have played Pokémon since the 1990s, provide insights into ways the Internet and other communication technologies have impacted the way they perceive and play Pokémon games. By grounding the nebulous idea of metaplay with 3 components, being metagaming, paratexts, and gaming capital, we can better understand contemporary digital play practices by integrating the communicative nature of the tools players use not only to play their games and expand their experience and knowledge, and how this works not only on a global, cultural level, but also the local, individual level.